Temperature-dependent phonon shifts in atomically thin MoTe2 nanosheets - Late, Dattatray J. (Applied Materials Today, 2016)
The present investigations deal with temperature-dependent Raman spectroscopy of bi-layer and few-layer molybdenum telluride (MoTe2) nanosheets prepared by micromechanical exfoliation method on a 300 nm SiO2/Si substrate. The temperature-dependent Raman spectroscopy was carried out using 633 nm laser excitation over the wider temperature range of 123-523 K. The temperature-dependent study illustrates the softening of A(1g), E-2g(1), and B-2g modes as temperature increases from 123 K to 523 K. The calculated temperature coefficients for A(1g), E-2g(1) and B-2g modes of the bi-layer MoTe2, nanosheet sample were found to be -0.00911 cm(-1) K-1, -0.01297 cm(-1) K-1 and -0.0159 cm(-1) K-1,respectively. For few-layer MoTe2 nanosheet sample, the temperature coefficient values were found to be -0.0113 cm(-1) K-1 (A(1g)), -0.0129 cm(-1) K-1 (E-2g(1)) and -0.0149 cm(-1) K-1 (B-2g), respectively. The present work highlights the temperature-dependent lattice vibration consequence of 2D MoTe2 nanosheet, which can be fundamentally pertinent in other promising and emerging 2D ultrathin layer and heterostructured materials to be used in future optoelectronic and nanoelectronic devices. (C) 2016 Elsevier Ltd. All rights reserved.
Keywords: Layered material; MoTe2; Phonon vibration; Raman spectroscopy; thermal effect